HARNESSING ARTIFICIAL INTELLIGENCE FOR HUMAN RIGHTS PROTECTION: ADVANCING SUSTAINABLE PLASTIC WASTE RECYCLING IN NIGERIA - Oludele Solaja (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
This paper explores the integration of artificial intelligence (AI) technologies with human rights considerations in plastic waste recycling, focusing on the context of Nigeria. Using an explanatory design and a basic review of the literature, it examines how AI can enhance human rights protection among workers in plastic waste recycling firms. The paper emphasizes the role of government policies and regulations in ensuring human rights protection, the need for ethical guidelines for AI use, and the potential of AI to improve worker safety and reduce environmental pollution in recycling facilities. Key recommendations for future research include enhancing AI capabilities for waste sorting, integrating Internet of Things (IoT) devices for real-time monitoring, and prioritizing ethics in AI development. Collaboration between stakeholders is identified as crucial, with multi-stakeholder partnerships and policy coherence essential for the effective implementation of AI technologies in plastic waste recycling. In conclusion, integrating AI with human rights considerations in plastic waste recycling is pivotal for enhancing efficiency, reducing pollution, and ensuring sustainable waste management practices. This paper contributes to the growing body of literature on AI and human rights in waste management, offering insights for policymakers, industry stakeholders, and researchers in Nigeria and beyond.